‘Through Valley of the Shadow of Death’: Death In-Between and Betwixt “Life After Life” in Mind Uploading Immortality - Chammah J. Kaunda; Minkyu Lee (Religions)
This article engages the concept of death as a revolutionary transformation within the contexts of mind uploading (MU) and Pierre Teilhard de Chardin’s theology of the Omega Point. The focus is not on the Omega Point itself as a conceptual endpoint, nor on what becomes of consciousness once it has been successfully uploaded into a digital substrate. To grasp the meaning of “death” within the context of MU, the article employs the notion of liminal speculative imagination to analyze death amid the liminality of biological mortality and digital immortality. It argues that death is more than just the end of life but rather as a transitional phase between different states of being. It contends that this liminal gap between life forms is an inherent aspect of existence that cannot be eliminated at a fundamental level. Instead of seeking to overcome death, the article suggests embracing the transformative nature of this liminality. In this view, death is seen as a natural and unavoidable part of life, serving as a mediator or catalyst for transitions into new forms of existence. Rather than focusing solely on achieving immortality, the article advocates for utilizing technology to facilitate evolution and advancement. By acknowledging the role of death in the process of transformation, particularly within the context of transhumanism, the article proposes that embracing liminality can lead to new possibilities for human evolution. This includes the potential emergence of transhuman life forms, such as those enabled by MU technologies.